English in a Post-Pandemic Context: The Case of Multilingual Filipino Day Care Children - Aireen Barrios (Languages)
Day care centers in Zamboanga City in western Mindanao, Philippines use the home language as a medium of communication as they carry out daily lessons for young children through songs, stories, games, and various social activities. Workers at the study’s day care site disclosed that the pandemic has significantly impacted language use among children in the community in favor of English. Internet connection and access to popular programs, particularly YouTube, have provided very young children easy access to English. As guardians and parents were forced to work from home at the height of the pandemic, the home became an extension of work, with most homes having a space for work using a laptop, a tablet, a cellphone, or other similar gadgets. It is within this set-up that children who were born between 2019 and 2020, who grew up within the lockdown period imposed by the deadly spread of COVID-19, and attended day care for the first time when they were around three to four years of age were observed to speak in English. Data from an experimental task where 3–4-year-old children were asked to describe animals using target language forms in Chabacano reveal that young Zamboangueño children spoke English most of the time. Excerpts from the data demonstrate how children generally spoke in English even while the task was delivered primarily in Chabacano. Demographic data and linguistic background of both the children and adults as provided by the parents or guardians of these children through a questionnaire help explain this phenomenon in greater detail. A closer look at the data reveals translanguaging at work among these multilingual children.